2004
DOI: 10.1002/srin.200405826
|View full text |Cite
|
Sign up to set email alerts
|

Friction Forces between Mould and Strand Shell during Billet Casting

Abstract: During continuous casting processes lubrication between mould and strand shell is very important for reaching and maintaining a good surface quality of both the as-cast strand and the finished product. The lubrication is influenced by the properties of the mould powder but also by the friction forces caused by the periodic movements of mould and the descending strand shell. In the present research measurements were carried out to investigate the friction forces during 150 mm sq. billet casting of different ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 3 publications
(1 reference statement)
0
14
1
Order By: Relevance
“…Friction force values obtained for Ø 170 mm billet were significantly higher than those mentioned in the literature [12].…”
Section: Object Of Studycontrasting
confidence: 66%
See 1 more Smart Citation
“…Friction force values obtained for Ø 170 mm billet were significantly higher than those mentioned in the literature [12].…”
Section: Object Of Studycontrasting
confidence: 66%
“…However, negative friction force which occurs at the positive step, is responsible for the pressure exerted upon the billet surface and contributes to closing the surface defects. In the course of the performed tests it was found that in some cases, in an upper position of the mould, the level of friction force could reach positive values approaching 5 kN [12].…”
Section: Object Of Studymentioning
confidence: 98%
“…On the other hand, with the same oscillation conditions, the necessary physical work to move the idle mould is also the same under the different oscillation modes, while the friction work is higher in sinusoidal mode than in non-sinusoidal mode. 5. If the friction force shows an abnormal trend and makes an obvious response, this advanced knowledge may be of great help to operators to avoid a breakout accident.…”
Section: Discussionmentioning
confidence: 98%
“…Investigation of the frictional behaviour is therefore essential to obtain a better online control of the mould processes. Under the conventional sinusoidal oscillation pattern, casting at higher speed may cause a decrease in flux powder consumption, and therefore increase the friction force, worsen the surface quality and even cause sticking breakouts [1][2][3][4]. The non-sinusoidal oscillation pattern has gradually been developed and applied in mould oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…Various research studies were published about non-sinusoidal oscillation theory, wave form, factor and application [4][5][6][7][8][9][10][11]. Theoretical analyses show that the features of non-sinusoidal oscillation in comparison with a sinusoidal pattern are the following: (1) As the positive strip time is longer, the rate of flux powder consumption increases and the friction force can be reduced; (2) The relative velocity of mould to the solidified shell in the positive strip period decreases, and accordingly the tension acting on the solidified shell is reduced; (3) In contrast, the relative velocity during the negative strip period increases, and the required level of the compressive force acting on the solidified shell will increase in the negative strip period. However, in some papers the research on friction force in non-sinusoidal oscillation is only in theory and insufficiently supported by measured data, and in some experimental papers the comparison of the periodical variety of friction force and some correlative parameters between the two kinds of 564 oscillation patterns is not taken into account.…”
Section: Introductionmentioning
confidence: 99%